Ultrasonic modification of polylactic acid and polyglycolic acid acupoint catgut embedding monofilaments for juvenile pseudomyopia. Issue 17 (September 2019) - Fu, Shaoju; Yang, Dongchao; Zhao, Cunyi; Zhang, Peihua
Acupoint catgut embedding therapy (ACET) has become the most promising method for treatment of juvenile pseudomyopia due to its advantages of lasting effect, high efficiency, safety and no side effects. However, poor hydrophilicity and biocompatibility are the main disadvantages, preventing ACET materials from having wide applications. This work fabricated four types of polylactic acid (PLA) and polyglycolic acid (PGA) monofilaments from their polymer chips, and then the prepared monofilaments were treated ultrasonically by dipping them in a mixed solution composed of ethyl alcohol and H2 O2 (volume ratio 1:1) at 250 W ultrasonic power for 30 min. Afterwards, the PLA and PGA groups were fully characterized with respect to structure characterizations, mechanical properties and in vitro properties. The results showed that the surface roughness of the monofilaments had been greatly enhanced by ultrasonic modification. The PLA groups' molecular structures changed little, while those of the PGA group emerged with some polar hydrophilic bonds. By deionized water measurement of contact angle values, the ultrasound modified PLA monofilaments (UMPLA1 = 87.2 ± 2.5°, UMPLA2 = 83.6 ± 3.5°) presented a decrease compared to that of untreated PLA ones (PLA1 =103.5 ± 3.4°, PLA2 = 108.4 ± 1.2°), while that of ultrasound modified PGA monofilaments (UMPGA1 = 75.6 ± 4.3°, UMPGA2 =70.5 ± 3.1°) was smaller than untreated PGA ones (PGA1 = 97.3 ± 1.7°, PGA2 = 95.8 ± 2.6°). Based on the measurement of the mechanical properties, the tensile properties and bending stiffness of the PLA and PGA groups changed little, and their swelling ratios were greatly improved after modification. All the prepared monofilaments presented non-toxicity with good cell viability (more than 75%), and samples UMPGA2 (81.4 ± 3.1%) and UMPLA2 (65.8 ± 0.8%) exhibited the largest cell attachment ratio values among their groups. In conclusion, these findings present important clinical implications regarding the ACET materials manufacturing process, which warrant further study.